Modern Electronic Journalism Helps People With Special Needs In The Republic of Kazakhstan - Kurmanbayeva, Almagul; Galiya, Maikotova; Noda, Larisa; Nazym, Eskuatova; Marzhan, Nurmanova (International Journal of Psychosocial Rehabilitation, 2020)
In the past years, the journalistic sphere has gone through radical changes and trans‐ formations, progressively adapting to the contemporary global trends in news‐making. Traditional understanding of journalism as a profession has changed significantly, mostly due to the fact that digital media environment has brought new opportunities but also challenges related to the journalistic practice. The text aims to offer a theoretical reflection on the issue of online journalism. At the same time, the chapter discusses specific forms of Internet‐delivered journalistic production and professional requirements placed on journalists who specialise in online news‐making, taking into consideration the current development tendencies of digital communication forms. The authors work with a basic assumption that many aspects related to form and content of online news need to be dis‐ cussed in the light of much needed terminological and paradigmatic revisions related to both the general theory of journalism and our practical understanding of journalism as a continual, creative and highly professional, publicly performed activity.